Czech alien flora and the historical pattern of its formation: what came first to Central Europe? - Pysek, Petr; Sádlo, Jirí; Mandák, Bohumil; Jarosík, Vojtech (Oecologia, 2003)
Temporal patterns of immigration to the country were analysed using 668 alien species in the flora of the Czech Republic for which the dates of the first record were available (64.8% of the total number of 1031 so-called neophytes, i.e. aliens introduced after the year 1500). After a period of initial slow increase lasting to the 1840s, the accumulation of neophytes over time could be best fitted by a linear model that explained 97% of the variance. The intensity of floristic research, which varied between periods, did not significantly affect the overall increase in the number of aliens. The effect of species traits on the year of introduction was evaluated, with continent of origin, introduction type (deliberate or accidental), life history, Grime's life strategy, onset of flowering, mode of dispersal and propagule size as explanatory variables. Species of European origin and CSR strategists arrived earlier than those with other origins and strategies. Deliberately introduced species appeared earlier than accidental arrivals, and those cultivated for utilitary reasons on average arrived earlier than ornamentals. Species capable of early flowering were remarkably more prevalent among early newcomers. A separate analysis of accidentally introduced American species also identified life history as a significant predictor of immigration time, with annuals being introduced earlier than biennials and perennials. The data contribute to an understanding of a crucial stage of the invasion process that has received little attention in the literature. The model "early alien" to Central Europe is a European species with a CSR strategy deliberately brought for cultivation as a utilitary plant. Once it escaped from cultivation, its establishment in the wild was favoured by its ability to flower early and, therefore, complete the life cycle.
Keywords: dějiny středověku; monitorování životního prostředí; rostliny; Survival; History, 16th Century; Reproduction; dějiny 16. století; ekosystém; History, Medieval; fyziologická adaptace; přežití; dějiny 20. století; Europe; History, 20th Century; Česká republika; Evropa; Environmental Monitoring; History, 15th Century; dějiny 17. století; Czech Republic; Plants; dějiny 19. století; dějiny 18. století; populační dynamika; History, 18th Century; History, 17th Century; dějiny 15. století; rozmnožování; Population Dynamics; History, 19th Century; Ecosystem; Flowers; květy; Adaptation, Physiological